Sporting females : critical issues in the history and sociology of women's sports - Hargreaves, Jennifer, 1937- (Routledge, 1994)
An outstanding contribution to feminist analysis of sport from the nineteenth century to the present day the author presents sport as a battle for control of the physical body and an important area for feminist intervention.